Safety and Efficacy of Nusinersen Focusing on Renal and Hematological Parameters in Spinal Muscular Atrophy - Hüseyin Bahadır Şenol; Gizem Yıldız; Ayşe İpek Polat; Adem Aydın; Ayşe Semra Hız; Alper Soylu; Uluç Yiş (Brain and Behavior)
ABSTRACT Background Spinal muscular atrophy (SMA) is a motor neuron disease caused by mutations in the SMN1 gene. Nusinersen, an antisense oligonucleotide, has been shown to improve motor function in SMA patients. However, concerns regarding its renal safety remain as previous studies have linked similar treatments to renal toxicity. Objective The aim of this study was to evaluate the effects of the nusinersen treatment on platelet counts and renal functions, specifically urine protein excretion, in SMA patients and to estimate safe urinary protein levels before administration of each intrathecal injection. Methods This retrospective study examined data from 33 patients with SMA to assess the effects of nusinersen on motor functions and laboratory parameters including platelet count, serum creatinine, urine protein, and urine creatinine. Measurements were taken at baseline andprior to each maintenance dose, after the completion of four initial loading doses. The baseline values were compared between SMA Type 1 and Type 2 patients, while the changes in these values over time were analyzed within each group. Results No significant adverse effects on platelet counts or renal functions were observed. Urine creatinine and protein levels were significantly higher in SMA Type 2 patients compared to SMA Type 1 at baseline; these parameters remained stable in SMA Type 2 but increased significantly after the loading doses in SMA Type 1. Motor function improvements were observed in both groups, with the most significant gains in SMA Type 1 after the loading doses. Thus, improvement in motor functions was associated with increase in urine creatinine. Conclusion Nusinersen treatment did not cause significant renal toxicity or affect platelet counts. Urine creatinine levels may serve as a potential biomarker for assessing treatment response in SMA Type 1.